Common Indications of Infant Admission at a Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Infants below one year are highly vulnerable to infections and malnutrition, influenced by biological, environmental and socioeconomic factors. Understanding disease patterns and associated determinants is crucial for targeted interventions. This study aims to assess the epidemiological pattern of common illnesses among infants below one year at Chattagram Maa-O-Shishu Hospital Medical College. Materials and methods: A hospital-based cross-sectional study was conducted on 453 infants aged below one year in Pediatric Department of Chattagram Maa O Shishu Hospital from 1st January 2024 to 31st December 2024. Data were collected using a structured questionnaire covering demographic information, socioeconomic status, presenting symptoms, and final clinical diagnoses. Statistical analysis was done in MS Excel and IBM SPSS version 24. Results: Among the 453 infants, 55% were male and 45% female. The majority were aged 1–3 months (37.1%) followed by 4–6 months (32%) and 7–12 months (30.9%). Mean ± SD = 5.28 ± 3.08 months. Most infants had normal birth weight (68%) and 58% were exclusively breastfed. Regarding maternal education, 22.1% had no formal education, 45% had primary education and 32.9% had secondary or higher education. In terms of socio-economic condition, 38% of families earned below 10,000 BDT monthly, 47% earned between 10,000–25,000 BDT and 15% earned more than 25,000 BDT. Urban residents accounted for 54.7% and 94.9% of the sample were Muslim. Common presenting symptoms included fever (62%) cough (47%) and diarrhea (36%). The leading diagnoses were respiratory tract infections (31%) followed by gastrointestinal disorders (25%) and associated with skin infections (15%). Conclusion: Infants admitted to Chattagram Maa-O-Shishu Hospital exhibited a high burden of respiratory and gastrointestinal conditions, with socio-demographic factors such as maternal education and feeding practices influencing health outcomes. Strengthening maternal education and promoting exclusive breastfeeding are key strategies to improve infant health in urban and peri-urban settings.Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 36-40